Mapping ESG Integration in Islamic Finance across D-8 Countries: A Bibliometric Perspective - Ebrima Khan; Amie Ceesay; Mian Muhammad Ajmal Khan (Universitas Airlangga, 2026)
Background: Concurrent global challenges have increasingly led to a paradigm shift from a traditional CSR focus to Environmental, Social, and Governance (ESG) practices aligned with long-term sustainability. Objective: This study tracks the evolution of trends and contributions of authors, affiliations, and countries to the ESG-Islamic finance literature across the Developing-8 countries between 2015 and 2024. Method: The Scopus database was used to extract 929 documents over 10 years, and a bibliometric review was conducted to identify current and future directions in ESG and Islamic Finance research. Results: The findings highlight a significant rise in ESG-Islamic finance research after the COVID-19 pandemic, with Malaysia and Indonesia leading in scholarly output. Conclusion: The analysis identified Hassan M.K. as the most productive author, Universiti Teknologi MARA as the highest-contributing institution, and Sustainable Switzerland as the most prominent journal. The research offers crucial insight for future researchers, policymakers, and financial practitioners working to strengthen ESG integration within the Islamic Finance Industry. Keywords: Bibliometric Review; Scopus database; D-8 countries; ESG integration; Islamic Finance.